The Scalable Commutativity Rule: Designing Scalable Software for Multicore Processors. - Clements, Austin T.; Kaashoek, M. Frans; Kohler, Eddie; Morris, Robert T.; Zeldovich, Nickolai (Communications of the ACM, 2017)
Developing software that scales on multicore processors is an inexact science dominated by guesswork, measurement, and expensive cycles of redesign and reimplementation. Current approaches are workload-driven and, hence, can reveal scalability bottlenecks only for known workloads and available software and hardware. This paper introduces an interface-driven approach to building scalable software. This approach is based on the scalable commutativity rule, which, informally stated, says that whenever interface operations commute, they can be implemented in a way that scales. We formalize this rule and prove it correct for any machine on which conflict-free operations scale, such as current cache-coherent multicore machines. The rule also enables a better design process for scalable software: programmers can now reason about scalability from the earliest stages of interface definition through software design, implementation, and evaluation.